Peningkatan Critical Thinking Mahasiswa dalam Mata Kuliah Akhlak Tasawuf melalui Pendekatan Problem Based Learning pada Perguruan Tinggi Swasta di Bantul - Badaruddin, A.; Ashari, Muh Subhan (IIQ An Nur Yogyakarta, 2024)
This research aimed to analyze in improving students' thinking in morals and Sufism courses by using problem-based learning approach and discussion method. This research was a mini research study using qualitative research methods and a case study approach. Data collection methods with observation interviews and documentation. There were two sources of data obtained, namely primary data obtained from observations and interviews, while secondary data was obtained by analyzing assignments made by students.The data analysis technique used the Miles and Huberman model. The results of this study were in the lecture of morals and Sufism by using a problem-based learning approach and discussion method succeeded in improving students' critical thinking. It was evident from the way of presenting material and student discussion from group one to group four continues to increase.